2022
DOI: 10.1111/den.14278
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of missed lesions in patients with inadequate bowel preparation through a very early repeat colonoscopy

Abstract: Objectives: When bowel preparation (BP) is inadequate, international guidelines recommend repeating the colonoscopy within 1 year to avoid missing clinically relevant lesions. We aimed to determine the rate of missed lesions in patients with inadequate BP through a very early repeat colonoscopy with adequate BP.Methods: Post hoc analysis was conducted using data collected from a prospective multicenter randomized clinical trial including patients with inadequate BP and then repeat colonoscopy. Inadequate BP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…While advanced adenoma detection is less affected (OR 0.74, 95% CI 0.62–0.87), proper bowel preparation remains crucial, particularly for identifying right‐sided, flat, and serrated lesions in some repeated colonoscopy studies 30 . Several studies have reported that inadequate or low‐quality bowel preparation is associated with an overall adenoma miss rate (AMR) of 40–48% during initial colonoscopies, and the advanced AMR was 10.9–27% 31–33 . Furthermore, inadequate bowel preparation may lead to prolonged procedures, more frequent repeat colonoscopies at shorter‐than‐recommended intervals, increased costs, lower CIRs, and a higher risk of electrocautery complications 24,34–37 .…”
Section: Quality Indicators Of Colonoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…While advanced adenoma detection is less affected (OR 0.74, 95% CI 0.62–0.87), proper bowel preparation remains crucial, particularly for identifying right‐sided, flat, and serrated lesions in some repeated colonoscopy studies 30 . Several studies have reported that inadequate or low‐quality bowel preparation is associated with an overall adenoma miss rate (AMR) of 40–48% during initial colonoscopies, and the advanced AMR was 10.9–27% 31–33 . Furthermore, inadequate bowel preparation may lead to prolonged procedures, more frequent repeat colonoscopies at shorter‐than‐recommended intervals, increased costs, lower CIRs, and a higher risk of electrocautery complications 24,34–37 .…”
Section: Quality Indicators Of Colonoscopymentioning
confidence: 99%
“…30 Several studies have reported that inadequate or low-quality bowel preparation is associated with an overall adenoma miss rate (AMR) of 40-48% during initial colonoscopies, and the advanced AMR was 10.9-27%. [31][32][33] Furthermore, inadequate bowel preparation may lead to prolonged procedures, more frequent repeat colonoscopies at shorter-than-recommended intervals, increased costs, lower CIRs, and a higher risk of electrocautery complications. 24,[34][35][36][37] Subpar bowel preparation significantly impacts costs, leading to a 12% and 22% increase at university and public hospitals, respectively, as revealed in Rex et al's analysis.…”
Section: Bowel Preparationmentioning
confidence: 99%
“…Currently, various bowel preparation drugs and methods are available to improve the effectiveness of bowel preparation; however, approximately 33% of patients still exhibit poor bowel cleansing in clinical practice 3 . This reduces the lesion detection rate and delays the diagnosis and treatment of intestinal diseases 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Digestive Endoscopy , Pantaleón Sánchez et al . reported a prevalence of missed lesions in patients who underwent early repeat colonoscopy with prior inadequate bowel preparation 4 . The investigation was a post‐hoc analysis of a prior multicenter randomized controlled trial (RCT) 5 .…”
mentioning
confidence: 99%
“…2,3 Unfortunately, there is insufficient evidence for the use of salvage strategy in patients with prior or expected inadequate bowel preparation.In this issue of Digestive Endoscopy, Pantale on S anchez et al reported a prevalence of missed lesions in patients who underwent early repeat colonoscopy with prior inadequate bowel preparation. 4 The investigation was a post-hoc analysis of a prior multicenter randomized controlled trial (RCT). 5 The study included patients with inadequate bowel preparation, defined as a score <2 in the Boston Bowel Preparation Scale (BBPS) in any segment, in baseline colonoscopies.…”
mentioning
confidence: 99%